New schemes for improving non data-aided symbol timing recovery for QAM receivers in flat fading channels - Nezami, M.K.; Sudhakar, R. (IEEE/AFCEA EUROCOMM 2000 : information systems for enhanced public safety and security, 2000)
In this paper we present a digital symbol timing synchronization algorithm based on maximum likelihood theory. The algorithm can be totally implemented in discrete time either by a DSP processor, or in a VLSI chip. The channel average fade duration (AFD) and level crossing rates (LCR) are incorporated into a new estimation approach that improves the symbol timing recovery. The schemes are: (1) smoothed post processing (SPP) estimates, and (2) fade envelope weighted (FEW) estimates. Both schemes incorporate fading statistics into the symbol estimator in order to enhance the estimate while the signal is in fade. We first present their implementations, then compare their performance using computer simulation experiments.